1998
DOI: 10.1074/jbc.273.48.31924
|View full text |Cite
|
Sign up to set email alerts
|

Differential Activation of p38 Mitogen-activated Protein Kinase and Extracellular Signal-regulated Protein Kinases Confers Cadmium-induced HSP70 Expression in 9L Rat Brain Tumor Cells

Abstract: We have reported that treatment with CdCl 2 at 40 -100 M induces the heat shock proteins (HSPs) in 9L rat brain tumor cells, during which the activation of heat shock factor (HSF) is essentially involved. By exploiting protein kinase inhibitors, we further analyzed the possible participation of specific protein kinases in the above processes. It was found that induction of HSP70 in cells treated with a high concentration of cadmium (i.e. 100 M) is preceded by the phosphorylation and activation of p38 mitogen-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 101 publications
(48 citation statements)
references
References 45 publications
0
48
0
Order By: Relevance
“…This conclusion is based on the following: (a) SB203580 did not prevent the generation of apoptosis by other agents, such heatshock and camptothecin, although the later one also caused p38 MAPK activation; (b) SB203580 did not prevent the generation of necrosis induced by the cadmium treatment of BSOpreincubated cells, although this treatment also increased p38 MAPK phosphorylation; and (c) SB203580 did not prevent the cadmium-provoked activation of the stress response. This later result was somewhat surprising, because SB203580 was reported to prevent HSF1 activation and HSP70 induction in rat brain tumor cells treated with high apoptosis-inducing cadmium concentrations (19). Such a discrepancy suggests the existence of marked differences in the regulation of the stress response in different cell types.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…This conclusion is based on the following: (a) SB203580 did not prevent the generation of apoptosis by other agents, such heatshock and camptothecin, although the later one also caused p38 MAPK activation; (b) SB203580 did not prevent the generation of necrosis induced by the cadmium treatment of BSOpreincubated cells, although this treatment also increased p38 MAPK phosphorylation; and (c) SB203580 did not prevent the cadmium-provoked activation of the stress response. This later result was somewhat surprising, because SB203580 was reported to prevent HSF1 activation and HSP70 induction in rat brain tumor cells treated with high apoptosis-inducing cadmium concentrations (19). Such a discrepancy suggests the existence of marked differences in the regulation of the stress response in different cell types.…”
Section: Discussionmentioning
confidence: 64%
“…Activation of Mitogen-activated Protein Kinases-Earlier observations indicated that cadmium caused a dose-dependent activation of ERK1/2 and p38 MAPK , as measured by their increased phosphorylation, in rat brain tumor cells (19). Hence, we decided to measure the phosphorylation/activation of those kinases in cadmium-treated U-937 cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the last decade, a growing body of evidence has accumulated suggests that in certain cell types micromolar concentration of Cd is able to initiate a series of rapid signaling events including: generation of second massagers (IP3, cAMP) within 15-30 sec (Smith et al,1989;Yamagami et al, 1998); increase in intracellular calcium within 3 min (Smith et al,1989;Yamagami et al, 1998); activation of certain kinases (Hung et al, 1998;Galan et al, 2000;Misra et al, 2002;; and induction of early response genes c-fos and c-myc within 30 min (Beyersmann and Hechtenberg, 1997;Misra et al, 2002;. Since these signals were generated soon after Cd exposure, it argued against a physiological interaction between Cd and intracellular proteins.…”
Section: Introductionmentioning
confidence: 99%